Góry jako przestrzenie sakralne. Tradycja i nowoczesność - Sztajer, Sławomir (Humaniora. Czasopismo Internetowe, 2024)
Mountains have always played an important role in the religiosity and spirituality of different cultures. They have been seen both as sacred spaces and as special bridges between the temporal and supernatural worlds, or as places that connect different cosmic levels. In religious traditions such as Hinduism, Buddhism, Christianity, and indigenous religions, mountains have been places of revelation, mystical experience, meditation, and worship. This article discusses the significance of mountains in selected traditional beliefs and rituals, emphasizing their role as material vehicles of spiritual heritage. This traditional approach is contrasted with contemporary ways of interpreting the sacredness of mountains, especially those interpretations shaped by secularization and modernization. Phenomena such as experiences of well-known alpinists and ordinary tourists, literary narratives and works of art show how the sacred character of mountains is adapting to modern realities.